1996
DOI: 10.1002/j.1460-2075.1996.tb01058.x
|View full text |Cite
|
Sign up to set email alerts
|

The helix-loop-helix transcription factor SEF-2 regulates the activity of a novel initiator element in the promoter of the human somatostatin receptor II gene.

Abstract: The effects of somatostatin hormones are mediated by a family of five different seven‐helix transmembrane spanning receptors (SSTR1–5). The expression of the five different SSTR subtypes displays a complex temporal‐ and tissue‐specific pattern. To investigate the molecular mechanisms controlling the different expression patterns of the SSTRs, we cloned the 5′‐flanking region of the human SSTR2 gene. Characterization of the SSTR2 promoter resulted in the identification of a novel initiator element (SSTR2inr). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 31 publications
1
43
1
Order By: Relevance
“…On the other hand, in other genes where an initiator-binding site has been functionally detected no motif resembling a conserved site is apparent (e.g. see [29]). A number of studies have identified various proteins as binding at or near the initiator motif, such as RNA polymerase II [3], YY1 [30], E2f(HIP1) [5], TAFII150 [1], USF [6], TFIIA [7], TFII-I [8,9] or TFIID itself [10][11][12], but the actual mechanisms of joint interaction of these proteins with the initiator (binding protein) and TFIID are obscure.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in other genes where an initiator-binding site has been functionally detected no motif resembling a conserved site is apparent (e.g. see [29]). A number of studies have identified various proteins as binding at or near the initiator motif, such as RNA polymerase II [3], YY1 [30], E2f(HIP1) [5], TAFII150 [1], USF [6], TFIIA [7], TFII-I [8,9] or TFIID itself [10][11][12], but the actual mechanisms of joint interaction of these proteins with the initiator (binding protein) and TFIID are obscure.…”
Section: Discussionmentioning
confidence: 99%
“…spliced forms of E2-2 proteins, with and without RSRS, are known to be expressed in different cells (23,24,33,34). The three cDNA clones (VL1, VL2, and VL3) isolated from human brain stem cDNA library represent the splice variant of E2-2 containing RSRS (Fig.…”
Section: In Vivo Effect Of E2-2 Proteins In U1240mg Cells On the Actimentioning
confidence: 99%
“…1). However, an E2-2 cDNA that lacks the sequence encoding RSRS was isolated from a murine brain cDNA library (33). Hence, the potential presence of both spliced 2, 7, and 12) or B (Ϫ484 to Ϫ467) (lanes 3, 8, and 13).…”
Section: In Vivo Effect Of E2-2 Proteins In U1240mg Cells On the Actimentioning
confidence: 99%
“…Ostensibly using in vitro assays, it was shown that TCF4 could bind and activate gene expression at the conserved E-box (Ephrussi-box, 5'-CANNTG) containing sequences in the enhancers or promoter regions of several genes [17,[29][30][31][32]. Although TCF4 has been shown to regulate gene expression at both canonical and synthetic promoters and enhancers, surprising little is known about TCF4's genomic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, TCF4-B has also been found to be a transcriptional repressor in different cell types [33][34][35]. However, it has been demonstrated that this isoform can also activate transcription in vitro, and therefore its function is highly context-dependent [30,36,37].…”
Section: Introductionmentioning
confidence: 99%